HUBUNGAN PENGETAHUAN PASIEN TENTANG STROKE DENGAN PENGELOLAAN FAKTOR-FAKTOR RISIKO PADA PASIEN STROKE DI RUMAH SAKIT UMUM DAERAH PANEMBAHAN SENOPATI BANTUL YOGYAKARTA - , MUMPUNI DYAH WARDHANI; , Heny Suseani P., S.Kp.,M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: One of risk factors of the the prevalence of stroke or recurrent stroke is hypertension which belongs to one of five major diseases at Panembahan Senopati Hospital. More fatalistic stroke attack is affected by oneâs knowledge on stroke whereby such knowledge can change someone in managing stroke or risk factors of stroke in the patient. Considering the importance of knowledge on stroke, it is necessary to study correlation between knowledge of patients on stroke and the management of risk factors in stroke patients at Panembahan Senopati Hospital Bantul Yogyakarta. Objective: To identify correlation between knowledge on stroke and the management of risk factors of recurrent stroke in stroke patients at Panembahan Senopati Hospital Bantul Yogyakarta. Method: The study was an analytic correlation with cross sectional design involving 20 patients of stroke at Panembahan Senopati Hospital. Samples were purposively selected. Knowledge on stroke was assessed using Stroke Recognition Questionnaire, whereas management of risk factors was assessed using instrument of risk factor management or self care. Data analysis used Spearman-Rank test. Result: The result of Spearman-Rank test showed there was no correlation between knowledge on stroke and the management of risk factors of stroke (p = 0,339, r = 0,225). The majority of respondents had good knowledge on stroke (80%). The management of risk factors of stroke in respondents partly belonged to good (50%) and partly poor (50%). Conclusion: There is no significant correlation between knowledge on stroke and the management of risk factors of stroke.